2017
DOI: 10.1128/aac.02665-16
|View full text |Cite
|
Sign up to set email alerts
|

Integron-Associated DfrB4, a Previously Uncharacterized Member of the Trimethoprim-Resistant Dihydrofolate Reductase B Family, Is a Clinically Identified Emergent Source of Antibiotic Resistance

Abstract: Whole-genome sequencing of trimethoprim-resistant Escherichia coli clinical isolates identified a member of the trimethoprim-resistant type II dihydrofolate reductase gene family (dfrB). The dfrB4 gene was located within a class I integron flanked by multiple resistance genes. This arrangement was previously reported in a 130.6-kb multiresistance plasmid. The DfrB4 protein conferred a Ͼ2,000-fold increased trimethoprim resistance on overexpression in E. coli. Our results are consistent with the finding that df… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 34 publications
1
40
0
Order By: Relevance
“…We previously identified the DfrB4 coding sequence, flanked by further antibiotic resistance genes, in a TMP-resistant North American clinical sample. 10 We further demonstrated that expression of DfrB4 in E. coli conferred complete resistance to the highest concentration of TMP that could be dissolved in the medium (600 μg/mL). 10 DfrB4 shares 77% amino acid identity with DfrB1; the catalytic core is highly conserved, whereas the loops and termini differ.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…We previously identified the DfrB4 coding sequence, flanked by further antibiotic resistance genes, in a TMP-resistant North American clinical sample. 10 We further demonstrated that expression of DfrB4 in E. coli conferred complete resistance to the highest concentration of TMP that could be dissolved in the medium (600 μg/mL). 10 DfrB4 shares 77% amino acid identity with DfrB1; the catalytic core is highly conserved, whereas the loops and termini differ.…”
Section: Resultsmentioning
confidence: 69%
“…These findings inspired the design of analogues that were confirmed to bind with 1:1 stoichiometry. We further revealed a broader biological impact by demonstrating that a second member of the DfrB family, identified in a North American TMP-resistant clinical sample, 10 is also effectively inhibited by these novel bisbenzimidazole inhibitors.…”
Section: Introductionmentioning
confidence: 89%
“…The DfrB4 protein, encoded by the integronrelated dfrB4 gene, was identified in antibiotic-resistant Escherichia coli clinical isolates. DfrB4 conferred a markedly increased resistance to the antibiotic trimethoprim in vitro, leading to the suggestion that dfrB4 contributes to clinical antibiotic resistance (21).…”
Section: Horizontal Transfer Of Drug-resistance Genesmentioning
confidence: 99%
“…These two families encode evolutionarily unrelated proteins of markedly different sizes. Sequence similarity indicates that dfrA genes are homologs of the chromosomally-encoded folA genes, whereas dfrB genes are functional analogs of unknown origin [23,24]. Most dfrA genes follow a standard naming convention consisting of dfrA followed by a numerical value indicating their discovery rank order.…”
Section: Introductionmentioning
confidence: 99%